ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN PT TEJO LOMANIS CILACAP - Herni Utami Rahmawati; Mutiasari; Essa Melissa (AmaNU: Jurnal Manajemen dan Ekonomi, 2022)
"Analysis of Factors Affecting Job Satisfaction of Employees of PT Tejo Lomanis Cilacap". Problem Formulation: 1. Does compensation affect the job satisfaction of employees of PT Tejo Lomanis Cilacap; 2. Does the work environment affect the job satisfaction of employees of PT Tejo Lomanis Cilacap; 3. Does communication affect the job satisfaction of employees of PT Tejo Lomanis Cilacap; 4. Does supervision affect the job satisfaction of employees of PT Tejo Lomanis Cilacap. Research Objectives: 1. To analyze the effect of compensation on job satisfaction of employees of PT Tejo Lomanis Cilacap; 2. To analyze the influence of the work environment on the job satisfaction of employees of PT Tejo Lomanis Cilacap; 3. To analyze the effect of communication on job satisfaction of employees of PT Tejo Lomanis Cilacap; 4. To analyze the effect of supervision on job satisfaction of employees of PT Tejo Lomanis Cilacap. This research is a case study using survey method. The data analysis technique uses Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Analysis, t-test. Compensation has an effect on employee job satisfaction; work environment affects employee job satisfaction; Communication has an effect on employee job satisfaction; Supervision affects the job satisfaction of employees of PT Tejo Lomanis Cilacap.